2016
DOI: 10.1093/ehjci/jew176
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood volume shunting in patients with atrial septal defects: assessment of heart function with cardiovascular magnetic resonance during dobutamine stress

Abstract: BackgroundThe purpose of this study was to determine the effect of stress on left-to-right shunting in patients with atrial septal defect (ASD) and to investigate if the degree of shunting, cardiac output (CO), and right ventricular (RV) volumes are related to exercise capacity.MethodsTwenty-six patients with a secundum ASD and 16 healthy volunteers were studied with rest/stress cardiac magnetic resonance using 20 µg/kg/min dobutamine and 0.25–0.75 mg atropine to quantify CO, pulmonary to systemic flow ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Two-dimensional PC-MR data of the ascending aorta from 17 healthy volunteers and 154 patients with heart failure (defined as left ventricular ejection fraction below 40%) were retrospectively included from a previous study of cardiac index (Carlsson et al, 2012). Two-dimensional PC-MR data of the pulmonary artery from 35 healthy volunteers and 25 patients with atrial septal defects were also included from a previous study of atrial septal shunt volumes (Stephensen et al, 2016). Vessel shape constraints and optimized algorithm parameters were extracted from 40 data sets, 20 from the ascending aorta group (10 healthy volunteers) and 20 from the pulmonary artery group (10 healthy volunteers).…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional PC-MR data of the ascending aorta from 17 healthy volunteers and 154 patients with heart failure (defined as left ventricular ejection fraction below 40%) were retrospectively included from a previous study of cardiac index (Carlsson et al, 2012). Two-dimensional PC-MR data of the pulmonary artery from 35 healthy volunteers and 25 patients with atrial septal defects were also included from a previous study of atrial septal shunt volumes (Stephensen et al, 2016). Vessel shape constraints and optimized algorithm parameters were extracted from 40 data sets, 20 from the ascending aorta group (10 healthy volunteers) and 20 from the pulmonary artery group (10 healthy volunteers).…”
Section: Methodsmentioning
confidence: 99%
“…During dobutamine stress, left‐to‐right shunting volume decreased which resulted in more balanced stroke volumes in the left and right ventricle (Stephensen et al ., ) and a larger increase in systemic compared to pulmonary cardiac index. Thus, during dobutamine stress, there was a greater increase in trans‐mitral flow compared to trans‐septal flow.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it is not known how increased workload affects longitudinal pumping in patients with ASD. Administration of dobutamine–atropine lowers the left‐to‐right shunt in ASD patients and subsequently the degree of RV volume overload (Stephensen et al ., ). Thus, studies in ASD patients with dobutamine–atropine may elucidate if the mechanisms of altered RV pumping physiology in the volume‐overloaded state is caused by the RV dilatation itself or if the different aetiologies of RV dilatation lead to different responses in pumping physiology.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the left‐to‐right shunt also causes inadequate left ventricular (LV) diastolic filling and reduced LV end‐diastolic volume due to right ventricular (RV) dilatation, leading to left‐sided heart failure because of insufficient LV stroke volume (LVSV) to maintain the blood flow necessary to meet the body's needs. In addition, a recent study showed that exercise capacity such as peak oxygen uptake, which is often used as a marker of the impact of the ASD after surgical or transcatheter ASD closure, correlates strongly with systemic cardiac output at rest and during low‐dose dobutamine stress in patients with ASD . Transcatheter closure of the ASD currently is widely considered to be the first‐choice therapeutic option due to its clear‐cut functional, safety, and social advantages .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study showed that exercise capacity such as peak oxygen uptake, which is often used as a marker of the impact of the ASD after surgical or transcatheter ASD closure, 3,4 correlates strongly with systemic cardiac output at rest and during low-dose dobutamine stress in patients with ASD. 5 Transcatheter closure of the ASD currently is widely considered to be the first-choice therapeutic option due to its clear-cut functional, safety, and social advantages. 6,7 Moreover, ASD closure results in normalized LV and RV geometry, and can increase LVSV.…”
Section: Introductionmentioning
confidence: 99%